CORONARY SLOW FLOW AND CHA2 DS2 -VASC-HSF SCORE IN STABLE ISCHEMIC HEART DISEASE - Pelin Karaca Özer; Mustafa Lütfi Yavuz; Emre Yalçın; Elif Ayduk Gövdeli; Mehmet Aydoğan; Samim Emet; Ali Elitok (Sabiad)
Objective: The coronary slow flow phenomenon (CSFP) and its causes are still not fully explained. We investigated the functionality and usefulness of the CHA2DS2-VASc-HSF score in the diagnosis of CSFP in stable ischemic heart disease.Material and Methods: Patients with no obstructive coronary artery disease (CAD) and CSFP detected as a result of coronary angiography were included in the study. Patients with CSFP were compared with those without. Coronary blood flow velocity was evaluated by calculating the TIMI frame count (TFC) from coronary angiography images. In addition to the traditional CHADS scores of the patients, the CHA2DS2-VASc-HSF score was also calculated.Results: According to our study results, the CHA2DS2-VASc-HSF score was higher in patients with CSFP than in those without (3.75±1.27 vs. 2.85±1.11; p<0.001). There was no difference between the CHADS2 and CHA2DS2-VASc scores of the two groups. In logistic regression models, Hs-troponin-T and CHA2DS2-VASc-HSF scores were determined as independent predictors of CSFP. CHA2DS2-VASc-HSF score and TFC were positively correlated in the CSFP group (r=0.848, p<0.001). The sensitivity of CHA2DS2-VASc-HSF was determined as 56%, the specificity was 74%, and the cut-off value was 3.5 in detecting the presence of CSFP.Conclusion: This study shows the association of CHA2DS2-VASc-HSF score with CSFP, suggesting that it can be used to predict CSFP and its severity